Effective elastic, thermoelastic, and piezoelectric properties of braided composites using equivalent laminate modeling. (4th July 2021) - Putra, Genio Odi; Hwang, Dae-Hyun; Han, Jae-Hung
Abstract : This paper presents an application of Equivalent Laminate Modeling (ELM) to predict the effective elastic, thermoelastic, and piezoelectric properties of braided composites. Here, two braided composite configurations were considered: biaxial and triaxial. The present ELM-based modeling was validated through a comparison with analytical unit cell modeling. In addition, a comparison with existing numerical and experimental results is also presented. As importantly, a technique to introduce an undulation effect into ELM using constant undulation angle is newly proposed. The results demonstrated the workability of using ELM to approximate the effective properties of braided composites predicted by considerably more sophisticated methods. An excellent approximation of unit cell analysis results highlights the capability of the proposed ELM with undulation effect.